Implementation of Adaptive Management To Improve The Quality of Process Standards In Inclusion Schools - Dewi, Desy Eka Citra; Elfahmi Lubis (JTP - Jurnal Teknologi Pendidikan, 2023)
Process standards are needed to improve and improve the quality of education. Inclusive schools as educational units are required to use national process standards, so that problems arise in the learning process for students with special needs. In order to provide equitable education services and to carry out effective and efficient learning, inclusive schools must be able to adapt learning to the needs of students with special needs. This study aims to determine the application of adaptive management in improving the quality of the standard process of inclusive schools. This research was conducted at SDIT Al Aufa Bengkulu City. This type of research is qualitative research, the research informants are school principals, deputy principals and teachers, the number of research informants is 31 people taken using a purposive sampling technique. Data collection is done through interviews, observation, and documentation. Data were analyzed using Miles and Huberman's model. The results of the study can be concluded that the implementation of adaptive management to improve the quality of the standard process of SDIT Al Aufa inclusive schools has been implemented properly, which is carried out in 4 forms of activities, namely: 1) lesson planning, 2) learning implementation, 3) learning evaluation, and 4) supervision learning. The process standards implemented at the SDIT Al Aufa inclusive school use national standards for regular students and school standards for students with special needs. It is hoped that inclusive schools will continue to encourage the development of an adaptive management system in every academic and non-academic process.